"RIPTIDE" — an innovative recoil-proton track imaging detector. (22nd September 2022) - Massimi, C.; Musumarra, A.; Leone, F.; Pellegriti, M.G.; Romano, F.; Spighi, R.; Villa, M.
Abstract: Neutron detectors perform key tasks in many research fields as nuclear, particle and astroparticle physics as well as neutron dosimetry, radiotherapy, and radiation protection. Neutron detectors exhibiting tracking capability are still missing, although several approaches to neutron momentum reconstruction have been proposed. In this context, we aim at developing a novel RecoIl-Proton Track Imaging DEtection system " RIPTIDE ", in which the light output of a fast scintillation signal is used to perform a complete reconstruction in space and time of the neutron-proton elastic scattering. The 3D track reconstruction is going to be implemented by state-of-the-art high-sensitivity imaging detector (CMOS, MCP-Timepix). Preliminary Geant4 simulations of the proposed set-up show up a good detection efficiency in a compact active volume. The envisaged electronic readout can be easily adapted according to a specific application (event-by-event mode or integration mode). The system can be rescaled by increasing the detection volume or by combining several detection modules. Further developments of the basic detection technique can be adapted for fast charged particle detection tracking as well.